2018
DOI: 10.26458/1815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monetary Policy on Economic Growth in Nigeria: An Empirical Investigation

Abstract: The study investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 3 publications
6
27
0
1
Order By: Relevance
“…The broad money supply (M2) as a monetary policy instrument increased economic growth by 91% and was also highly statistically significant. This finding was in consonance with other studies like Ufoeze, Odimgbe, Ezeabalisi and Alajekwu (2018) and that Inam and Ime (2017) which revealed that money supply was a much more viable monetary policy instrument, in comparison to the MPR. The coefficient of inflation rate which represented the control variable in the model followed apriori expectation, as it retarded economic growth by 17%.…”
Section: Ardl Long-run Resultssupporting
confidence: 91%
“…The broad money supply (M2) as a monetary policy instrument increased economic growth by 91% and was also highly statistically significant. This finding was in consonance with other studies like Ufoeze, Odimgbe, Ezeabalisi and Alajekwu (2018) and that Inam and Ime (2017) which revealed that money supply was a much more viable monetary policy instrument, in comparison to the MPR. The coefficient of inflation rate which represented the control variable in the model followed apriori expectation, as it retarded economic growth by 17%.…”
Section: Ardl Long-run Resultssupporting
confidence: 91%
“…money supply increased concurrently with domestic credit over the last five years from 2015 to 2019 (KNBS, 2019) and this supports empirical evidence that monetary policy, which has an effect on bank liquidity, is a key determinant of bank credit(Akinlo & Oni, 2015;Ufoeze, Odimgbe, Ezeabalisi, & Alajekwu, 2018).…”
supporting
confidence: 62%
“…This was consistent with Srithilat and Sun (2017) and Perera (2016). However, Ufoeze (2018) found that the monetary policy rate and the interest rate have an insignificant positive relationship on economic growth. This was in line with Nyamonga, Sichei, and Mutai (2008), Mutuku and Koech (2014) and Kamaan and Nyamongo (2014).…”
Section: Literature Reviewmentioning
confidence: 99%